Tradisi Semana Santa di Larantuka Sebagai Daya Tarik Wisata Rohani: Peran Budaya dan Religi Dalam Pariwisata Lokal - Natalia Kristiani Tandafatu; Rosalina Andriyani Ebang Pareira; Paulus Nong Wisang (Universitas Nusa Nipa Maumere, 2026)
Semana Santa (Holy Week), which commemorates the passion, death, and resurrection of Jesus Christ, has evolved not only as a sacred religious ritual but also as a unique spiritual tourism attraction. This study aims to analyze the cultural and religious roles in the development of local tourism, with a specific case study on the Semana Santa tradition in Larantuka, East Flores. The research method used is qualitative with a literature study approach, by collecting and analyzing data from various relevant literature sources. The research results indicate that Semana Santa functions as a primary tourism attraction through four key factors: (1) Sacred Rituals and Processions (such as the Tuan Ma and Tuan Ana processions) that create profound spiritual experiences; (2) Culture and Tradition, which represent a unique acculturation between Catholic rituals and the local Lamaholot culture; (3) Historical Value as a living heritage that has endured for over five centuries; and (4) Spiritual Experience that attracts pilgrims to pray and seek blessings. The conclusion of this study is that the integration of culture, religion, and tourism within the Semana Santa tradition has become a significant driver of the local economy by promoting the growth of homestays, culinary offerings, and souvenirs